Black Sand-Based Photocatalyst for Hydrogen Production from EDTA Solutions Under UV–Vis Irradiation (2020)
Black sand from coastal deposits composed by a mixture containing oxides (Fe2O3, TiO2, SiO2, ZrO2, MnO, Al2O3, etc.) and metals (V, Cr, Ni, Sr, Ce, etc.). Both this mineral, as well as a fraction obtained from it, have been used as a photocatalyst for hydrogen production from EDTA (electron donor agent) solutions under UV/Vis irradiation. The physical, chemical and optical properties of materials were studied by X-ray fluorescence, scanning electron microscopy/energy-dispersive X-Ray analysis, BET area, thermal gravimetric analysis, X-ray diffraction patterns, Fourier transform infrared and UV–Vis spectroscopy techniques. The effect of several variables, such as chemical composition (Fe/Ti atomic ratio), catalyst dosage, initial pH of suspension, and sacrificial agent (EDTA) concentration on photocatalytic hydrogen production using these minerals were evaluated. The hydrogen production rate was favored by the high content of iron and low initial pH. Catalyst dosage and sacrificial agent concentration show a synergistic effect due to free radicals generated by the photocatalytic mechanism and the turbidity of the suspension (optical depth). In acidic conditions, M1 fraction produced 35,459.78 µmol g⁻¹ (0.5 g l⁻¹ catalyst and 10 mM EDTA), while lowest hydrogen production (350.294 µmol g⁻¹) was obtained using the same sacrificial agent concentration but employing 0.1 g l⁻¹ of M1 at natural pH suspension (pH 4.8). The results are promising since the hydrogen levels produced by this natural ore are close to yields obtained under similar conditions, using synthetized semiconductors. It’s highlight, that in this study a natural catalyst (principle of the geocatalysis), that not was substantially modified. Graphic Abstract